PENGARUH IKLIM KERJA DAN KEPEMIMPINAN TERHADAP KINERJA DOSEN PADA FAKULTAS EKONOMI UNIVERSITAS TRIDINANTI PALEMBANG - Alinadia . (Fakultas Ekonomi Universitas Tridinanti Palembang, 2014)
ABSTRACTÃ‚Â This Research is to know the influence between Work Climate and Leadership either through parsial and also by simultan to Lecture Performance at Economic Faculty of Tridinanti University Palembang. The result are (1). Anticipated a Work Climate positively and real have an effect on to Lecture Performance at Economic Faculty of Tridinanti University Palembang, (2). Anticipated a Leadership potively and real have an effect on to Lecture Performance at Economic Faculty of Tridinanti University Palembang, (3). Anticipated Work Climate and Leadership by together influence the Lectures Performance at Economic Faculty of Tridinanti University Palembang. This Research population is entire Lectures at Economic Faculty of Tridinanti University Palembang amounting to 69 peoples, while sample research taken by 30 peoples by using random technique. Instrument of data collection used is enquette using scale Likert compiled by pursuant to construction which embrace from various theory realized by into variable operacional, while examination to instrument research conducted passing validity test and realibility test. Analyse the data conducted bay passing conditions test consisted of the normality test using test of Kolmogrov Smirnov, test the homogeneity by using test of Chi Square, and test the linearity using One-Way Anova. Examination Hipotesis conducted by used analyse the regresi and correlation of variable of Leadership Style and Work Climate as free variable to Lectures Performance as variable trussed.Ã‚Â Keywords : Work Climate, Leadership, PerformanceÃ‚Â